Transition‐Metal‐Carbide (Mo2C) Multiperiod Gratings for Realization of High‐Sensitivity and Broad‐Spectrum Photodetection. (16th September 2019) - Jeon, Jaeho; Choi, Haeju; Choi, Seunghyuk; Park, Jin‐Hong; Lee, Byoung Hun; Hwang, Euyheon; Lee, Sungjoo
Abstract: A novel hybrid phototransistor consisting of molybdenum carbide (Mo2 C) and molybdenum disulfide (MoS2 ) is proposed. By exploiting the interface properties of MoS2 and Mo2 C, a highly sensitive and broad‐spectral response photodetector is fabricated. The underlying mechanism of the enhanced performance is the efficient hot carrier injection from Mo2 C to MoS2 . The strong coupling of MoS2 and Mo2 C at the interface provides the significantly low Schottky barrier height (≈70 meV), which gives rise to the significantly efficient hot carrier transfer from Mo2 C to MoS2 . The grating of metallic Mo2 C produces plasmonic resonance, which provides hot carriers to the MoS2 channel. By adjusting the grating period of Mo2 C (400–1000 nm), the optimal photoresponse of light can be controlled, from visible to NIR. By integrating various Mo2 C multigrating periods (400–1000 nm) with MoS2, a novel photodetector is demonstrated with high responsivity (R > 10 3 A W −1 ) and light‐to‐dark current ratio (>10 2 ) over a broad spectral range (405–1310 nm). The proposed novel hybrid photodetector, 2D semiconductors with multigrating 2D metallic stripes, exhibits high sensitivity and broad spectral detection of light and can overcome the inherent weakness of conventional 2D photodetectors, paving the way forward for next‐generation photoelectric devices. Abstract : A hybrid photodetector consisting of a 2D semiconductor (MoS2 ) integrated with multiple grating metallic stripes (Mo2 C) demonstrates high sensitivity and broad spectral detection of light, overcoming the inherent weakness of conventional 2D photodetectors and opening up possibilities for next‐generation photoelectric device technology by providing new functionalities for high sensitivity and effective broad‐spectrum photodetection.